Equilibrium and Kinetic Adsorption of Organic Compounds onto Organobentonite: Application of a Surface Diffusion Model - Raúl Ocampo-Pérez; Roberto Leyva-Ramos; Erika Padilla-Ortega (Adsorption Science & Technology)
The equilibrium and kinetic adsorption of Methylene Blue (MB), Methyl Blue (MTB) and 1-naphthalene sulphonic acid (NSA) onto organobentonite was investigated. The effect of pH on the adsorption capacity was studied by determining the adsorption isotherm over the pH range 3–12. The results showed that the maximum adsorption capacity at 25 °C of the organobentonite towards the removal of the compounds studied occurred at pH = 3 for MTB and NSA and at pH = 11 for MB. The experimental adsorption rate data were interpreted via a diffusional model that considered the external mass transport, intra-particle diffusion and adsorption onto an active site, intra-particle diffusion being considered as both pore volume and surface diffusion. The surface diffusion model fitted the experimental data quite well, thereby indicating that the overall rate of adsorption was controlled by surface diffusion. Furthermore, the surface diffusion coefficient increased by augmenting the mass of MB, MTB and NSA adsorbed at equilibrium. In addition, the surface diffusion model was used to interpret experimental data cited in the literature, thereby showing that surface diffusion plays an important role in the adsorption of organic compounds onto organoclays.